On Basu's proposal: Fines affect bribes - Sergey V. Popov (Cardiff University, Cardiff Business School, 2017)
I model the connection between the equilibrium bribe amount and the fines imposed on both bribe-taker and bribe-payer. I show that Basu's (2011) proposal to lower the fines imposed on bribe-payers in order to induce more whistleblowing and increase the probability of penalizing corrupt government officials might instead increase bribe amounts. Higher expected fines on bribe-takers will make them charge larger bribes; at the same time, lowering fines for bribe-paying might increase bribe-payers' willingness to pay bribes.
Keywords: H8; K4; 330; corruption; bribery; extortion; decentralization; fines